2011
DOI: 10.1519/jsc.0b013e3181ecd033
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Hormone and Immune Responses to Three Resistance Exercise Schemes in Elite Female Athletes

Abstract: This study examined the salivary hormone and immune responses of elite female athletes to 3 different resistance exercise schemes. Fourteen female basketball players each performed an endurance scheme (ES-4 sets of 12 reps, 60% of 1 repetition maximum (1RM) load, 1-minute rest periods), a strength-hypertrophy scheme (SHS-1 set of 5RM, 1 set of 4RM, 1 set of 3RM, 1 set of 2RM, and 1set of 1RM with 3-minute rest periods, followed by 3 sets of 10RM with 2-minute rest periods) and a power scheme (PS-3 sets of 10 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 28 publications
3
28
0
11
Order By: Relevance
“…Cortisol also displayed no significant level of change after the highvolume exercise, which was concurrent with results obtained by others (24). Although some researchers have noticed changes in levels of cortisol in blood and saliva after resistance exercise (30)(31)(32)(33), samples in these studies were taken either immediately or shortly after (a few hours) exercise. Changes in cortisol levels may have occurred at time intervals different from the one chosen for our study.…”
Section: Discussionsupporting
confidence: 83%
“…Cortisol also displayed no significant level of change after the highvolume exercise, which was concurrent with results obtained by others (24). Although some researchers have noticed changes in levels of cortisol in blood and saliva after resistance exercise (30)(31)(32)(33), samples in these studies were taken either immediately or shortly after (a few hours) exercise. Changes in cortisol levels may have occurred at time intervals different from the one chosen for our study.…”
Section: Discussionsupporting
confidence: 83%
“…Accordingly, cortisol responses are now extensively used as a biomarker of mental and physical stress and have been suggested to be useful for following stress and recovery in athletes (33). Previous investigations have also shown that highly demanding exercise increases the resting cortisol levels (10,25,32). To date, however, no studies have reported on the cortisol responses to training and competition in highlevel futsal players.…”
Section: Introductionmentioning
confidence: 99%
“…As 10 que encontraram elevações nas concentrações deste hormônio nos 3 protocolos de esforço físico empregados: esforço de endurance (4 séries de 12 repetições a 60% de 1RM e 1 minuto de intervalo), hipertrofia (uma série com intensidades proporcionais a 5RM, 4RM, 3RM, 2RM e 1RM com 3 minutos de intervalo e seguidas por três séries de 10RM com 2 minutos de intervalo) e potência (três séries 12 estudaram o comportamento do cortisol (pré e na recuperação: imediatamente após: IP e a 60 minutos) em três protocolos de exercício resistido: hipertrophy (H: quatro séries de 10 repetições a 75% 1RM com 90 segundos de intervalo), strenght (S: 11 séries de três repetições a 90% de 1RM e cinco minutos de intervalo) e Power (P: oito séries de seis repetições a 0% 1RM com três minutos de intervalo) em um único exercício resistido: agachamento. Os autores observaram elevações nas concentrações de cortisol em IP somente no protocolo H e concluíram que tal comportamento seja devido à intensidade do esforço físico, pois resultou em maior atividade muscular que os demais acarretando elevações nas concentrações cortisol.…”
Section: Resultsunclassified
“…Dentre estas adaptações são observadas elevações nas concentrações plasmáticas dos hormônios cortisol e hormônio do crescimento (GH) 7,8 , como também reduções nas concentrações plasmáticas de insulina 9 . Muitos trabalhos estudam o comportamento hormonal em diferentes modelos de treinamento (hipertrofia e força) 10 , de intensidade com diferentes percentuais de uma contração voluntária máxima (1RM) 11 , de duração de intervalos 12 e de exercícios executados: leg press (LP), agachamento, supino reto (SR), flexão e extensão do joelho entre outros, entretanto os ajustes ainda não são totalmente claros; os exercícios LP e SR merecem maior atenção pois são amplamente utilizados em diferentes programa de treinamento físico. Todavia ainda não está bem claro a magnitude das respostas hormonais após uma sessão de exercício resistido padrão de LP e SR. Há necessidade de estudar o comportamento destes hormônios devido a trabalhos apresentarem resultados contraditórios entre os hormônios cortisol, GH e insulina.…”
Section: Artigo Originalunclassified
See 1 more Smart Citation